Genomics and Network Analysis of Multidrug-Resistant Shigella flexneri from Raw Vegetables in Bangladesh for Risk Assessment and Targeted Therapeutic Intervention - Islam, K M Tanjida; Shahin Mahmud (Universitas Muhammadiyah Surakarta, 2025)
Shigella flexneri increasingly poses a threat to public health in developing nations through the dissemination of multidrug-resistant (MDR) strains via contaminated raw vegetables in urban agriculture systems. Despite extensive characterization of clinical isolates, the mechanistic insights and therapeutic vulnerabilities of food-borne S. flexneri strains from Bangladesh remain underexplored. Therefore, this study aimed to characterize MDR S. flexneri from Bangladeshi raw vegetables retrieved from the NCBI genome database and identify core and essential antibiotic-resistant genes as prioritized therapeutic targets. Whole-genome sequences of four S. flexneri strains isolated from tomatoes and green chilies across Gazipur and Dhaka were retrieved from NCBI GenBank and analyzed through comparative genomics to identify core genes and resistance determinants. Networks were constructed using the STRING database, followed by centrality-based topology analysis to identify hub genes that cross-referenced with the KEGG database and the Database of Essential Genes. Comparative analysis revealed 4273 core genes and 44 antibiotic resistance genes across all strains. Network topology analysis identified eight hub genes (tolC, acrA, emrK, yegO, yjcP, emrB, yjcR, evgS) based on degree, closeness, and betweenness centrality metrics. Five hub genes (tolC, acrA, emrK, emrB, evgS) were classified as essential for bacterial survival, representing critical nodes in efflux-mediated resistance and two-component regulatory systems. These essential hub genes constitute high-priority therapeutic targets whose disruption could compromise multidrug resistance mechanisms and bacterial viability in food-borne S. flexneri. Additionally, to mitigate their dissemination, raising public awareness on MDR pathogens from raw vegetables is recommended.